CCR VII Text and Codicology - Phillips, Kim (Journal of Semitic studies, 2025)
The present study offers a fresh edition of CCR VII: two conjugate leaves from a Leviticus manuscript, in Christian Palestinian Aramaic (CPA), preserved in palimpsest form in Codex Climaci Rescriptus. The CPA undertext was re-read with the aid of multispectral images. In addition to the re-edited text, a brief codicological study of the manuscript is offered, as well as a linguistic commentary and text collation.